Peningkatan Efisiensi Penggunaan Bahan Bakar Terhadap Produktivitas Hasil Proses Penyulingan Sereh Wangi Menggunakan Sistem Kohabasi Untuk Mendukung Kegiatan Agro-Industri - Eko Poerwanto; Kris Hariyanto (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2022)
One way to isolate essential oils from essential oil-producing plants is by distillation. Distillation is the separation of components in the form of a liquid consisting of two or more kinds of mixtures based on differences in boiling points. The process is carried out on essential oils that are not soluble in water. The distillation process that has been used so far is by using steam and water, because the equipment construction is cheaper and simpler. However, steam and water distillation has a disadvantage, namely that it requires more water vapor. This will result in a certain amount of steam condensing in the plant tissue so that the material will get wetter so that it will increase the use of fuel and will reduce the productivity of the distillation process. To overcome this, it is necessary to strive for a more effective distillation system.This research was conducted with the aim of increasing the combustion efficiency of the essential plant distillation process, namely citronella, so that it is expected to increase the productivity of the distillation. This research was carried out by changing the distillation system using the cohobation system. Boyolali.The results showed that the efficiency of the kohobasi furnace distillation system was 0.85% higher than the steam distillation system, these results were in line with the productivity level of the citronella oil distillation production process, so for the work program of the Guli Village Government it was recommended to use the kohobasi furnace distillation system